ANALISIS KEPUASAN MAHASISWA S2 PENDIDIKAN SAINS TERHADAP LAYANAN UNIVERSITAS NEGERI SURABAYA MENGGUNAKAN METODE SERVQUAL DAN IMPORTANCE-PERFORMANCE ANALYSIS (IPA) - Nurhaddi, Raka Prasetyo; Roesminingsih, Erny; Amalia, Kaniati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the satisfaction level of Master of Science Education students at the Faculty of Mathematics and Natural Sciences, Surabaya State University (UNESA) with the quality of institutional services. This service quality measurement integrates the empirical Service Quality (SERVQUAL) and Importance-Performance Analysis (IPA) methods. The approach used is descriptive quantitative through a cross-sectional survey design. Questionnaires were distributed to 83 respondents randomly selected using the Single Sign-On (SSO) authentication system. The results of the Wilcoxon significance test indicate a significant difference between student expectations and the actual services received. Systematically, the gap analysis recorded a negative overall average score (Grand Mean) of -0.07, which confirms that actual services have not succeeded in meeting user expectations. The most fundamental weaknesses were found in the dimensions of responsiveness and empathy. Furthermore, the IPA quadrant mapping revealed operational allocation inefficiencies, where the institution provides excessive services to low-priority attributes (Quadrant IV). In conclusion, this study recommends reallocating resources from Quadrant IV toward improving essential services at the top priority crisis point (Quadrant I). This step is crucial for building a service ecosystem that is proportional, managerially efficient, and relevant to the dynamic needs of students.